2010
DOI: 10.1590/s0004-28032010000400008
|View full text |Cite
|
Sign up to set email alerts
|

NM23 protein expression in colorectal carcinoma using TMA (tissue microarray): association with metastases and survival

Abstract: -Context -NM23, a metastasis suppressor gene, may be associated with prognosis in patients with colorectal carcinoma.Objective -To analyze NM23 expression and its association with the presence of lymph node and liver metastases and survival in patients operated on for colorectal carcinoma. Methods -One hundred thirty patients operated on for colorectal carcinoma were investigated. Tissue microarray blocks containing neoplastic tissue and tumor-adjacent non-neoplastic mucosa were obtained and analyzed by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The protein expression of nm23 was assessed in the colorectal carcinoma tissue by immunohistochemistry. This revealed that the protein expression was higher in carcinoma tissue compared with that in adjacent non-neoplastic mucosa, similar to the results of a previous study (14).…”
Section: Discussionsupporting
confidence: 91%
“…The protein expression of nm23 was assessed in the colorectal carcinoma tissue by immunohistochemistry. This revealed that the protein expression was higher in carcinoma tissue compared with that in adjacent non-neoplastic mucosa, similar to the results of a previous study (14).…”
Section: Discussionsupporting
confidence: 91%
“…In CRC many studies managing small series of patients have centred on the tissue expression of NDKA as a prognostic factor for metastasis, with inconclusive results25283031323334.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of metastasis suppressor gene nm23 was shown to be higher in neoplastic colorectal carcinoma tissue compared to the adjacent non-neoplastic mucosa, exhibiting a correlation with longer disease-free survival (28). The overexpression of nm23 may be involved in carcinogenesis and a decrease in nm23 expression was previously shown to be associated with metastasis of GI carcinoma (29).…”
Section: Metastasis-associated Genesmentioning
confidence: 92%